1977
DOI: 10.1107/s0567739477000680
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and ordering in Fe1−xO

Abstract: Samples in the composition range Fe0.gsO-Feo.880 quenched from about 1000°C, have been studied by electron diffraction/microscopy with special emphasis on the dark-field technique. The set of morphologies obtained by quenching and annealing confirms a spinodal-like decomposition in an oxygen-rich and an almost stoichiometric component. The diffraction spots and dark-field images reveal a considerable degree of order which is enhanced upon heat treatment below 300°C. Previous diffraction studies have been inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 6 publications
(10 reference statements)
2
40
0
Order By: Relevance
“…(b) Generally, it has been shown that the long-range ordering is not cubic; a (2.5X, 2-5X, 5)0 superstructure has frequently been observed linked with the presence of stacking faults for values of z close to 0.09-0.10 (Andersson & Sletnes, 1977;Ishiguro & Nagakura, 1985.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Generally, it has been shown that the long-range ordering is not cubic; a (2.5X, 2-5X, 5)0 superstructure has frequently been observed linked with the presence of stacking faults for values of z close to 0.09-0.10 (Andersson & Sletnes, 1977;Ishiguro & Nagakura, 1985.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: pshen@mail.nsysu.edu.tw. assemble into larger units (e.g., 13:4, 16:5 and form a paracrystal (4,5)) which order further into Fe O spinel or other ordered phases: p and p (6,7). (The paracrystalline distribution is such that the spacing between defect clusters tends to be maintained fairly constant but relative lateral translations may occur more variably; hence, there is negligible di!raction intensity beyond "rst order (4,5).…”
Section: Introductionmentioning
confidence: 98%
“…5) According to the previous results obtained by X-ray diffraction, neutron diffraction, transmission electron microscope (TEM) and computer simulation, defect clusters are periodically arranged every 2.5-2.7a 0 (a 0 is the lattice parameter of the rock-salt type FeO). [6][7][8][9][10][11][12] However, there are only limited reports on the surface structures of bulk Fe 1-x O. The surface crystal structures of Fe 1-x O were only studied in terms of a thin film on a substrate using scanning tunneling microscope (STM), low energy electron diffraction (LEED) and/or Auger electron spectroscopy (AES).…”
Section: Introductionmentioning
confidence: 99%